Analisis Manajemen Klaim Jaminan Hari Tua (JHT) di BPJS Ketenagakerjaan Kantor Cabang Pratama Rantau Prapat - Dwiki Wardana Syah; Maryam Batubara (MIMBAR ADMINISTRASI FISIP UNTAG Semarang, 2024)
Old Age Security (JHT) is an important program in the social security system in Indonesia which is organized by the Employment Social Security Administering Agency (BPJS). Despite being a vital form of social protection, JHT claims management is often in the spotlight due to the various challenges it faces, including effectiveness, efficiency and fairness in disbursement of claims. In this context, this research aims to analyze JHT claims management at the Pratama Rantau Prapat BPJS Employment Branch Office. This study uses a qualitative research method with a case study approach. Data was collected through direct observation, interviews with officers and participants, as well as analysis of documents related to the claims process. The research results show that the JHT claims process faces various challenges, including the long time it takes to complete a claim, a lack of transparency and communication, and gaps in understanding between participants and officers. The conclusion of this research is that significant improvements are needed in JHT claims management. Recommendations for improvement include increasing process efficiency, increasing transparency and communication, and simplifying claims procedures. Implementation of these recommendations is expected to improve the quality of JHT claims services and provide greater benefits for participants in their preparation for a more financially secure retirement.